Drivers and barriers to the adoption and diffusion of Sustainable Jet Fuel (SJF) in the U.S. Pacific Northwest. (January 2017) - Smith, P.M.; Gaffney, M.J.; Shi, W.; Hoard, S.; Armendariz, I. Ibarrola; Mueller, D.W.
Abstract: Sustainable Jet Fuel (SJF) represents an important component of the airline industry's strategy to simultaneously reduce GHG emissions while meeting a growing demand for international air travel. SJFs also have the potential to provide fuel supply diversification and security, enhance fuel price stability and provide regional/rural economic development benefits. This paper measures and ranks perceived drivers and barriers to an economically viable SJF industry in a unique U.S. region, the U.S. Pacific Northwest (PNW), through personal interviews with key aviation fuel supply chain stakeholders conducted from June to September 2015. In addition to providing a fertile arena for this first effort to systematically assess these drivers and barriers, the U.S. PNW is unique due to the region's long strategic focus on aviation innovation and its importance to the regional economy, the seminal efforts in the region to outline a path forward on SJF beginning in 2010, and the relatively small population spread over a large geographic area with a limited number of "hub" airport nodes which geographically concentrates aviation fuel demand and distribution. Nineteen stakeholder interviewees acknowledge that, in order for regional SJF adoption-diffusion to occur, airline jet fuel buyers must drive the process, particularly as they deal with greenhouse gas (GHG) emission issues and related policy considerations. Important perceived barriers to SJF industry scale-up in the U.S. PNW include the high production costs of SJF and related issues, such as fuel logistics and quality control in the transport, storage, and blending of SJFs. Perceptions around chain-of-custody issues, such as blending, tracking, and crediting of SJFs and future SJF market share projections for the year 2030 were also examined. Incorporating stakeholder input into discussions about adding blended SJF into the U.S. aviation fuel supply provides needed insight for the biofuels industry, policymakers, and researchers. Highlights: Drivers and barriers to SJF in the U.S. Pacific Northwest (PNW) are examined. Chain-of-custody issues and future SJF market share projections are examined. Airlines are perceived to be the predominant driver of SJF in the PNW region. High cost (price) of SJF vs. petro-jet was the most-mentioned barrier. Blended SJF logistics issues are complex and misperceptions may be widespread.